Study the effect of pressure on flammability limits of acetylene - Nurul Bazlinda, Bazalan (2012)
Flammability limits are one of the factors that commonly considered in fuel properties for applications in gases industry.The objective of this study is to determine affect atmospheric pressure on flammability limits of acetylene and also to determine flammability limits range of acetylene when manipulated pressure (below 1 atm).This study is very important due to pressure is one of the parameter that affect flammability limits.These experiments were performed in 20 L closed explosion vessel.Material use in this study is pure acetylene, air and 10J igniter.The igniters were ignited mixtures by spark permanent wire at center of the vessel.Explosion pressure data and graph were analyzed to determine the flammability limit ranges of acetylene.Major finding in this study is upper flammability limit will increase in increase of pressure without significant changes in lower flammability limits.Significance from this study is it can determine the suitable condition and flammability limits for operating of acetylene.Thus,the risk of incident in industry can possibly be reduced.As a conclusion,it is proven that the pressure is one of the parameter that was give effect to flammability limits of fuel.